An analysis of the compliance by the Lesotho Defence Force with the convention against torture and other cruel, inhuman or degrading treatment or punishment - Sechele, Bulane Andrew (Department of Public Law, 2026)
This study analyses the compliance by Lesotho, especially the Lesotho Defence Force (the LDF), with the Convention against Torture and Other Cruel, Inhuman or Degrading Treatment or Punishment (the CAT) of 1984. It discusses the prohibition of torture in the international arena and how this is reflected in Lesotho, especially in the LDF.